Audio Signature in Graphical Password Authentication System - Avanish Kumar Singh, Deepasree P O (International Journal of Scientific Research and Management (IJSRM), 2013)
Graphical passwords, which consist of clicking or dragging activities on the pictures rather than typing textual characters, might be the option to overcome the problems that arise from the text-based passwords system. An important usability goal for knowledge-based authentication systems is to support users in selecting passwords of higher security, in the sense of being from an expanded effective security space. User is asked to select a sound signature, which helps the user in order to remember the click-points during login phase even if the user tries to login after a long time, and a tolerance dimension during password creation process. Persuasion is used to influence user choice in click-based graphical passwords, encouraging users to select more random, and hence more difficult to guess, click-points.